HVOR GÅR CHOLOS HEN, NÅR DE GÅR UD? Folklore og identitet blandt storbymigranter i Peru - Pærregaard, Karsten (Tidsskriftet Antropologi, 1997)
Karsten Pærregaard: Where do Cholos go when They Leave? Folklore and Identity among Urban Migrants in Peru An important term in the description of Peru’s ethnic groups is cholo, a category indicating urban migrants trying to distance themselves from their Andean past and obtain recognition as citizens in the country’s major cities. Conventionally, cholo has been considered a transitional status for Peru’s indigenous population which wants to cast off its Indian identity and become westemized. This article argues against such a notion and suggests that cholofication is a permanent identity for the majority of Peru’s rural and urban population. The article draws on material gathered among migrants whose origins are in a village in the Southern highland and analyzes how the migrants use folklore festivals and parades to change the negative image the surrounding society holds of them as cholos. The article concludes that only when all those regarded as cholos recognize their status as such and replace the negative import of the term with a more positive content, will a new identity be visible and cholo lose its former meaning in social and theoretical discourse.